Navigating Challenges Strategies for Enhancing English Teaching in Central Lombok's Primary Schools - Herayana, Desi; Suryaningsih, Hartati (Jurnal Ilmiah Telaah, 2025)
This study investigates the challenges faced by English teachers in primary schools in Central Lombok and identifies strategies to address these issues. Key barriers include limited teaching resources, socio-economic disparities, and large class sizes, all of which hinder effective English instruction. Teachers face diverse student proficiency levels, cultural influences prioritizing traditional rote-learning methods, and professional isolation that limits collaborative opportunities. The study employs qualitative methods, combining semi-structured interviews with 10 English teachers and structured classroom observations. Interviews explored topics such as resource limitations, training disparities, and student engagement strategies, while classroom observations provided empirical insights into teacher-student interactions, instructional methods, and resource availability. Data were analyzed thematically to ensure a comprehensive understanding of the contextual challenges. Findings highlight the need for professional development programs focused on culturally responsive pedagogies and strategies for addressing linguistic diversity. Collaborative networks and community involvement are recommended to bridge the gap between global English standards and local cultural contexts. By integrating these approaches, this research advocates for targeted interventions to enhance English teaching and learning outcomes in Central Lombok's primary schools.